Sex on wheels: sexuality experiences and discourses of men in wheelchairs - Jenniffer Karolinny de AraÃjo Dantas (2016)
The objective of this study is to analyze how men with spinal cord injury experience their sexuality from a different body/identity as paraplegia or quadriplegia, taking into account the interference of erotic and effective exchanges in these experiments. In this dissertation, I develop my narrative from personal and social conflicts these individuals, also showing other forms of vision for the handicapped, wich are linked to the bodies of deviante eroticism and pornography of disability. The methodology used resulted from a need from their own field of study, so the nethnography was the most convenient tool, because it allows interation through the internet, wich provided greater accessibility to and interlocutors. Firstly, the interviews were in person and later mediated by videoconferencing.